Microleakage of Glass Ionomer based Restorative Materials in Primary Teeth: An In vitro Study - Ayna, B.; Celenk, S.; Atas, O.; Tumen, E. C.; Uysal, E.; Toptanci, I. R. (Wolters Kluwer Medknow Publications, 2018)
Aim: Using AutoCAD, we examined the microleakage of dye at the edges of primary-teeth restorations using three glass ionomer-based restorative materials. Materials and Methods: A total of 30 extracted noncarious primary molars were used. Class V cavities were adjusted on the buccal surfaces. The teeth were randomly divided into three groups of 10 teeth each as follows: Group A (Ketac Molar), Group B (Photac Fil), and Group C (Dyract XP). All specimens were stored for 24 h at 37 degrees C in distilled water. The teeth were thermocycled 1000 times between 5 degrees C +/- 2 degrees C and 55 degrees C +/- 2 degrees C before immersion in 0.5% basic fuchsin for 24 h. Two mesiodistal cuts of each tooth were photographed under a stereomicroscope equipped with a digital camera. The dye-infiltrated surface area was measured. Statistical evaluations were performed by the Kolmogorov-Smirnov test, Levene test, one-way analysis of variance, and Tukey's honestly significant difference test. Results: The mean microleakage ratio differed significantly among the groups (P < 0.05). Group C exhibited a significantly smaller area (P < 0.001) than the other groups. Group A had a nonsignificantly higher mean microleakage value than Group B (P > 0.05). Conclusions: Polyacid-modified composite resin may be a useful restorative material in primary teeth in terms of minimizing microleakage.
Keywords: Glass ionomer-based restorative materials; microleakage; primary teeth